2004
DOI: 10.1002/cjoc.20040220708
|View full text |Cite
|
Sign up to set email alerts
|

A relative study on two‐photon absorption properties of C60 and C70

Abstract: We have theoretically investigated the one-and two-photon absorption properties of Cm and CT0 using the ZKNDO method. From the results it is suggested that the one-photon absorption specka are in agreement with the experimental observations. It is found that the maximum TPA cross section of C70 is more than twice that of Cm.which is consistent with the experimental results. A notable point is that the TPA process of Cm is different from that of C70 as well as other ordinary conjugated molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The results in the tables also reveal that the TPA cross-sections of the F−C molecule in both symmetries are about 10 3 −10 5 times larger than the TPA cross-section of a bare fullerene molecule, which clearly indicates that one can modulate the TPA parameters by utilizing weak π-stacking interactions. Previously, a number of theoretical as well as experimental works were carried out on various fullerenes, e.g., C 60 , C 70 , etc., and their derivatives. The results of ZINDO calculations in combination with the sum-over-all-states approach for fullerene (C 60 ) suggested that, in the wavelength range 400−1000 nm, it has only one TPA active mode with cross-section 1000 GM at 518 nm wavelength, and that the other TPA modes are very weak . In this work, we found that all the TPA modes of fullerene are very weak in the wavelength range studied, 675−855 nm.…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…The results in the tables also reveal that the TPA cross-sections of the F−C molecule in both symmetries are about 10 3 −10 5 times larger than the TPA cross-section of a bare fullerene molecule, which clearly indicates that one can modulate the TPA parameters by utilizing weak π-stacking interactions. Previously, a number of theoretical as well as experimental works were carried out on various fullerenes, e.g., C 60 , C 70 , etc., and their derivatives. The results of ZINDO calculations in combination with the sum-over-all-states approach for fullerene (C 60 ) suggested that, in the wavelength range 400−1000 nm, it has only one TPA active mode with cross-section 1000 GM at 518 nm wavelength, and that the other TPA modes are very weak . In this work, we found that all the TPA modes of fullerene are very weak in the wavelength range studied, 675−855 nm.…”
mentioning
confidence: 53%
“…Previously, a number of theoretical as well as experimental works were carried out on various fullerenes, e.g., C 60 , C 70 , etc., and their derivatives. [22][23][24][25] The results of ZINDO calculations in combination with the sum-over-all-states approach for fullerene (C 60 ) suggested that, in the wavelength range 400-1000 nm, it has only one TPA active mode with cross-section 1000 GM at 518 nm wavelength, and that the other TPA modes are very weak. 24 In this work, we found that all the TPA modes of fullerene are very weak in the wavelength range studied, 675-855 nm.…”
mentioning
confidence: 99%
“…In 1992, Tutt and Kost first reported the optical limiting performance of C 60 and C 70 solutions. , While nonlinear optical processes such as 2PA and nonlinear refraction could play some roles, the mechanism that is primarily responsible for the optical limiting properties of the fullerenes has been attributed to the so-called reverse saturable absorption (RSA), which is a linear absorption process where the excited-state absorption is much greater than the ground-state absorption. However, C 60 and some higher fullerenes, e.g., C 70 , have been shown experimentally and theoretically , to possess two-photon properties. Although many organic derivatives of C 60 were reported in the literature, multiphoton absorptivity was reported only for a few of their derivatives.…”
Section: 5 Fullerenesmentioning
confidence: 99%
“…It appears that the reverse saturable absorption dominates in the shorter-wavelength region (440−560 nm) whereas 2PA dominates in the longer-wavelength region (580−1000 nm). , Using a continuous tunable 100 fs pulse laser to measure the time-resolved degenerate four-wave-mixing (DFWM) spectra of both amorphous film C 60 and C 70 , Dalton et al reported that the 2PA coefficients at the resonance maxima were about the same, with a value of ∼20 ± 8 cm/GW. ,, A recent theoretical study on the 2PA property of C 60 , which was based on the equilibrium geometry optimized at the B3LYP/6-31G level and the ZINDO method combined with a SOS formula (see eqs 19−21) to calculate the second hyperpolarizability and the 2PA cross section of C 60 , suggested that, in the 400−1000 nm range, there is only one 2PA peak at 518 nm with a large cross section of about 1000 GM . A similar theoretical treatment of C 70 suggested that its maximum 2PA cross section is more than twice that of C 60 , which is consistent with the experimental measurement …”
Section: 5 Fullerenesmentioning
confidence: 99%
“…Compared with C 60 , C 70 has higher electron affinity and higher possibility to form anions or free radicals because of the reduced symmetry structure 18 . In addition, C 70 has a larger photo cross-sectional area, which suggests that a high light harvesting efficiency can be achieved 19 . Latest studies revealed that C 70 -TiO 2 hybrids show a significant photocatalytic activity for degradation of organic pollutant in visible light region 20 21 .…”
mentioning
confidence: 99%